2016
DOI: 10.1136/bmjopen-2016-011907
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of approaches to using patient experience data for quality improvement in healthcare settings

Abstract: ObjectivesExplore how patient-reported experience measures (PREMs) are collected, communicated and used to inform quality improvement (QI) across healthcare settings.DesignSystematic review.SettingVarious primary and secondary care settings, including general practice, and acute and chronic care hospitals.ParticipantsA full range of patient populations from (children through to the elderly) and staff (from healthcare practitioners to senior managers).MethodsScientific databases were searched (CINAHL, PsycINFO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
239
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(250 citation statements)
references
References 24 publications
(143 reference statements)
7
239
0
4
Order By: Relevance
“…Overall, these negative associations conveyed a withdrawal of participants' willingness to use the app when their personal information reaches the public domain, or when the intention to use of their data is unclear. The results from this study suggest that individuals are more willing to share sensitive information, if the use of their data was to support research activity and or could have the potential to reduce medical errors [22,26,42].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Overall, these negative associations conveyed a withdrawal of participants' willingness to use the app when their personal information reaches the public domain, or when the intention to use of their data is unclear. The results from this study suggest that individuals are more willing to share sensitive information, if the use of their data was to support research activity and or could have the potential to reduce medical errors [22,26,42].…”
Section: Discussionmentioning
confidence: 88%
“…Existing literature identified three overarching themes into which barriers and enablers of digital technology uptake were categorised. These three themes were broadly: service delivery to consumers [2, [16][17][18][19][20][21]; technology facilitation by staff members [2, 13,[22][23][24][25][26][27]; and strategic organisational factors [1-3, 18, 22, 24, 28-30]. The barriers and enablers identified were dependent on the purpose and objectives of each study.…”
Section: Methodsmentioning
confidence: 99%
“…This is not surprising, since designing specific interventions to improve patient experience in daily practice is a yet to be accomplished mission. Two systematic reviews recently concluded that actual interventions to improve patient experiences are rare (Davidson et al, ; Gleeson et al, ). Also in Belgium, patient experiences, although frequently measured, have not been part of any formal quality improvement method.…”
Section: Discussionmentioning
confidence: 99%
“…Around one‐third of patient complaints relate to staff‐patient relationships such as communication, empathy, courtesy, consideration and compassion demonstrated by front‐line staff; these aspects of care are critical for positive patient experiences . Evidence suggests, however, that patient experience data currently available in the NHS tend to be used to stimulate changes in care processes which are technical in nature, rather than tackling the more difficult task of changing clinician behaviour …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Evidence suggests, however, that patient experience data currently available in the NHS tend to be used to stimulate changes in care processes which are technical in nature, rather than tackling the more difficult task of changing clinician behaviour. 8 Although staff are unlikely to intentionally behave in ways that are detrimental to the patient experience, they may lack insight into how their behaviours affect patients or how to modify those behaviours. One approach for promoting insight and change is reflective learning.…”
Section: Introductionmentioning
confidence: 99%